TINJAUAN PERISTIWA CYBER CRIME YANG TERJADI PADA TAHUN 2019 DI KOTA SAWAHLUNTO - Futra, Yumelfi (UNES Law Review, 2020)
Cyber ​​Crimeis a form of virtual crime by utilizing computer which connected to the internet network, and exploiting other devices or computers that is connected to the internet. Cybercrime was previously regulated in the regulation Number 36 Year 1999 concerning Telecommunications, however this regulation has not been able to accommodate virtual and computer crimes. To anticipate the development of information technology, regulation Number 19 Year 2016 concerning Amendments to regulation Number 11 of 2008 concerning Electronic Information and Transactions was issued. In Sawahlunto City in 2019, several cyber-crime incidents were found, such as online extortion, fraud through online , and theft of Wi-Fi wireless streams, therefore a research was conducted on how the cyber-crime events that occurred in Sawahlunto City in 2019 , regulations governing cyber, the causes and obstacles in handling the cyber-crime. The data used are secondary supporting data collected through library research and primary data as supporting data which is carried out through field studies with interview techniques. The results showed that: the discovery of cyber-crimes that occurred in Sawahlunto City in 2019 such as online extortion, online fraud and theft of Wi-Fi wireless streams, knowing the regulations on cyber-crime, namely the ITE Regulation and knowing the factors and obstacles in handling cyber-crimes that occurred in the City Sawahlunto in 2019.